PENGARUH BRAND IMAGE DAN PRODUCT QUALITY TERHADAP LOYALITAS PELANGGAN SEMEN DYNAMIX DI KOTA BATAM - NOVITA ANDARWATI SITORUS; REALIZE . (JURNAL ILMIAH KOHESI, 2020)
This research aims to find out empirically about the influence of brand image, and product quality on customer loyaltyDynamix cement simultaneously. In addition to knowing the effect of brand image and product quality on customer loyalty,this research was conducted at PT Solusi Bangun Indonesia Tbk Batam. The number of samples used in this study was 183.The instrument used to collect data was a questionnaire. The sampling technique used is Purpose sampling where thesample is taken based on predetermined criteria. By using validity and reliability tests to test data quality, linear analysis anddetermination coefficients (R) are used to experiment with classical assumptions and to test their effects, while using t testsand F tests to test hypotheses with the help of SPSS version 25. The coefficient determination results ( R2) shows that brandimage and product quality affect 38.3% of customer loyalty. Meanwhile it can be seen that brand image affects 17.2% andproduct quality affects 44.2% in customer loyalty from multiple linear regression. The conclusion based on the results of thisresearch and discussion is that brand image has a positive and significant influence on customer loyalty, product quality hasa positive and significant effect on customer loyalty and simultaneously brand image and product quality have a significanteffect on customer loyalty.